Studying “Modeling” in Fostering Students’ Writing Capability in Writing Simple Descriptive Paragraph - Hariadi Syam; Muhammad Yunus (Universitas Negeri Makassar, 2021)
The objectives of this research was to find out why students' ability to write simple descriptive paragraphs is improved by modeling in the second year of MTs Negeri Kolaka. The report's aim was to gather information and data about the students' ability to write concise descriptive paragraphs by modeling.This research used a collaborative Classroom Action Research design (CAR). It happened in the first semester of the academic year 2019-2020. The emphasis of this research was on classes VIII and 8. There were 23 students in this group. The writing test and observation sheet were the instruments used in the study. In order to collect data, the researcher conducted research from the first to the second cycle. The data was analyzed using qualitative methods.According to the result of the research, modeling in the second year of MTs Negeri Kolaka could enhance the students' ability to write clear descriptive paragraphs. The paper concluded an increase in the number of students writing. The outcome of the writing test provided by the researcher at the last meeting in terms of product could be seen in terms of product. The students got an average score of 48.52 on the pre-test. It increased to 63,30 in the first period and 75,13 in the second. Every meeting's outcome observation sheet revealed that teaching and learning activities were growing. Based on the analysis of the observation sheet, the average score was found to be 3,7. It belongs to the equal group in the first cycle. It was at 4,7% at the time. It belongs to the positive party in the second cycle.